Biocompatible and antibacterial Flammulina velutipes-based natural hybrid cryogel to treat noncompressible hemorrhages and skin defects - Zhu, Yufan; Chen, Feixiang; Wu, Minhao; Xiang, Jieyu; Yan, Feifei; Xie, Yuanlong; Tong, Zan; Chen, Yun; Cai, Lin (Frontiers in Bioengineering and Biotechnology, 2022)
Hemorrhage, infection, and frequent replacement of dressings bring great clinical challenges to wound healing. In this work, Flammulina velutipes extract (FV) and hydroxyethyl cellulose (HEC) were chemically cross-linked and freeze-dried to obtain novel HFV cryogels (named HFVn, with n = 10, 40, or 70 corresponding to the weight percentage of the FV content), which were constructed for wound hemostasis and full-thickness skin defect repair. Systematic characterization experiments were performed to assess the morphology, mechanical properties, hydrophilic properties, and degradation rate of the cryogels. The results indicated that HFV70 showed a loose interconnected-porous structure and exhibited the highest porosity (95%) and water uptake ratio (over 2,500%) with a desirable degradation rate and shape memory properties. In vitro cell culture and hemocompatibility experiments indicated that HFV70 showed improved cytocompatibility and hemocompatibility. It can effectively mimic the extracellular matrix microenvironment and support the adhesion and proliferation of L929 cells, and its hemolysis rate in vitro was less than 5%. Moreover, HFV70 effectively induced tube formation in HUVEC cells in vitro. The results of the bacteriostatic annulus confirmed that HFV70 significantly inhibited the growth of Gram-negative E. coli and Gram-positive S. aureus. In addition, HFV70 showed ideal antioxidant properties, with the DPPH scavenging rate in vitro reaching 74.55%. In vivo rat liver hemostasis experiments confirmed that HFV70 showed rapid and effective hemostasis, with effects comparable to those of commercial gelatin sponges. Furthermore, when applied to the repair of full-thickness skin defects in a rat model, HFV70 significantly promoted tissue regeneration. Histological analysis further confirmed the improved pro-angiogenic and anti-inflammatory activity of HFV70 in vivo. Collectively, our results demonstrated the potential of HFV70 in the treatment of full-thickness skin defects and rapid hemostasis.